2007
DOI: 10.1080/13632750701664277
|View full text |Cite
|
Sign up to set email alerts
|

Managed moves: schools collaborating for collective gain

Abstract: Government guidance in the United Kingdom encourages groups of schools to take collective responsibility for supporting and making provision for excluded pupils and those at risk of exclusion. Managed-moves are one way that some schools and authorities are enacting such guidance. This paper presents the results of an evaluation of one such scheme. The scheme, involving seven neighbouring secondary schools, was nearing its first year of completion. The paper draws primarily on interview data with pupils, parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The idea of a fresh start and the possibilities of growth offered by a change in circumstances is also a key theme in resilience research; Rutter (2013) highlights that key turning points in people's lives (such as changing schools) bring the possibility of developing along a different path with the interaction between the person and the experiences offered by the new situation influencing outcomes. This dynamic view of a fresh start echoes the findings of (Vincent et al 2007) who concluded that it is not the move to a new school itself but the process of the managed move which underpins its success.…”
Section: Developing Practicesupporting
confidence: 59%
See 3 more Smart Citations
“…The idea of a fresh start and the possibilities of growth offered by a change in circumstances is also a key theme in resilience research; Rutter (2013) highlights that key turning points in people's lives (such as changing schools) bring the possibility of developing along a different path with the interaction between the person and the experiences offered by the new situation influencing outcomes. This dynamic view of a fresh start echoes the findings of (Vincent et al 2007) who concluded that it is not the move to a new school itself but the process of the managed move which underpins its success.…”
Section: Developing Practicesupporting
confidence: 59%
“…It seems likely that making preparations for incoming pupils conveys that they are a part of the school and that their teachers care about them (Libbey 2007). The respectful and inclusive ethos characterised by such a sensitive and flexible response to academic and non-academic needs is suggested to be a key intervention in promoting belonging and has been shown to be linked to positive outcomes of managed moves (Shochet et al 2011;Vincent et al 2007). …”
Section: Generating a School Identitymentioning
confidence: 98%
See 2 more Smart Citations
“…Cuts to local authority provision, the development of school-run collaborative processes for young people excluded from school, the growth of 'managed moves' programmes (Abdelnoor, 2007;Harris, Vincent, Thomson, & Toalster, 2006;Vincent, Harris, Thomson, & Toalster, 2007) and a recent trial to test out schools' capacity to commission all of their own alternative education provision (Institute of Education (University of London) and the National Foundation for Educational Research ( NFER), 2013) have all contributed to a significant increase in complementary AE. This expanded AE is either run by schools themselves or with a small group of 'preferred providers' (Institute of Education (University of London) and the National Foundation for Educational Research ( NFER), 2014).…”
Section: Alternative and Complementary Alternative Educationmentioning
confidence: 99%